Wireless Charger for Small Scale Rechargeable Battery - Johan, Muhammad Nuruddin; Othman, Nordiana Azlin; Jamail, N.A.M (Evolution in Electrical and Electronic Engineering, 2022)
Wireless power transfer (WPT) technologies enable power transfer between electrical networks without the use of wires or exposed connectors. A wired connection restricts their mobility and, in some situations, may not be a secure choice if they are damaged. The project aims to create a wireless charger that can be used to charge a variety of small rechargeable batteries, and its focus is on near-field wireless power transfer. Two circuits, which are the transmitter circuit and receiver circuit, are constructed for the wireless charger for small-scale rechargeable batteries. Thereby, the oscillator circuit in the transmitter circuit enabled it to generate AC power and a high frequency of approximately 180 kHz, while the full bridge rectifier circuit in the receiver circuit enabled it to generate a 5V DC voltage. The system’s performance reduced as the distance between the transmitter coil and receiver coil increased. In conclusion, the WPT idea can decrease the use of cable, which reduces power transfer efficiency because of power loss. To prevent the battery from being overcharged, which might harm the battery, a cut-off system can be added to the receiver circuit, which can automatically stop charging when the battery is full.